2010
DOI: 10.1525/jer.2010.5.3.43
|View full text |Cite
|
Sign up to set email alerts
|

Why Do We Pay? A National Survey of Investigators and IRB Chairpersons

Abstract: The principle that payment to participants should not be undue or coercive is the consensus of international and national guidelines and ethical debates; however, what this means in practice is unclear. This study determined the attitudes and practices of IRB chairpersons and investigators regarding participant payment. One thousand six hundred investigators and 1900 IRB chairpersons received an invitation to participate in a web-based survey. Four hundred and fifty-five investigators (28.3%) and 395 IRB chair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Although compensation remains a contentious issue within the literature (Festinger et al, 2005; Fry & Dwyer, 2001; McKeganey, 2001; Pandya & Desai, 2013; Permuth-Wey & Borenstein, 2009; Ripley et al, 2010), our findings have important implications for how research compensation is approached. Specifically, our findings highlight the need to determine what constitutes equitable compensation for research participation, particularly when recruiting structurally vulnerable populations (e.g.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Although compensation remains a contentious issue within the literature (Festinger et al, 2005; Fry & Dwyer, 2001; McKeganey, 2001; Pandya & Desai, 2013; Permuth-Wey & Borenstein, 2009; Ripley et al, 2010), our findings have important implications for how research compensation is approached. Specifically, our findings highlight the need to determine what constitutes equitable compensation for research participation, particularly when recruiting structurally vulnerable populations (e.g.…”
Section: Discussionmentioning
confidence: 80%
“…For structurally vulnerable populations, compensation remains highly contentious despite a wealth of literature exploring its tenuous impact on research (Festinger et al, 2005; Fry & Dwyer, 2001; McKeganey, 2001; Pandya & Desai, 2013; Permuth-Wey & Borenstein, 2009; Ripley, Macrina, Markowitz, & Gennings, 2010). Structurally vulnerable populations, such as people who use drugs (PWUD) and people living with HIV (PLHIV), occupy marginalized positions within larger social hierarchies based on socio-structural inequities (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 20% of Irish RECs reported to have policies or guidelines regarding payment of research participants, compared with 66.4% of US-based IRBs 7. Cultural differences in both healthcare delivery and research practices may be relevant in this respect; 94% of research organisations based in the USA reported to offer payment to participants in ‘some’ projects 11.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers generally turn to research ethics committees (RECs) for guidance on whether and how to pay research participants appropriately; however, only 66.4% of institutional review boards (IRBs) in the USA report to have guidelines in place themselves 7. The Health Service Executive of Ireland has concluded that there is a need for standardisation of the Irish REC approval processes 8.…”
Section: Introductionmentioning
confidence: 99%